School environment, sedentary behavior and physical activity in preschool children - Sara Crosatti Barbosa; Diogo Henrique Constantino Coledam; Antonio Stabelini Neto; Rui Gonçalves Marques Elias; Arli Ramos de Oliveira
Abstract Objective: To analyze physical activity and sedentary behavior in preschool children during their stay at school and the associated factors. Methods: 370 preschoolers, aged 4-6 years, stratified according to gender, age and school region in the city of Londrina, PR, participated in the study. A questionnaire was applied to principals of preschools to analyze the school infrastructure and environment. Physical activity and sedentary behavior were estimated using accelerometers for five consecutive days during the children's stay at school. The odds ratio (OR) was estimated through binary logistic regression. Results: At school, regardless of age, preschoolers spend relatively more time in sedentary behaviors (89.6-90.9%), followed by light (4.6-7.6%), moderate (1.3-3.0%) and vigorous (0.5-2.3%) physical activity. The indoor recreation room (OR 0.20, 95%CI 0.05-0.83) and the playground (OR 0.08, 95%CI 0.00-0.80) protect four-year-old schoolchildren from highly sedentary behavior. An inverse association was found between the indoor recreation room and physical activity (OR 0.20, 95%CI 0.00-0.93) in five-year-old children. The indoor recreation room (OR 1.54, 95%CI 1.35-1.77), the playground (OR 2.82, 95%CI 1.14-6.96) and the recess (OR 1.54, 95%CI 1.35-1.77) are factors that increase the chance of six-year-old schoolchildren to be active. Conclusions: The school infrastructure and environment should be seen as strategies to promote physical activity and reduce sedentary behavior in preschool children.